The impact of physical activity, diet and stress on acne vulgaris. Pathogenesis and therapeutic procedures - Karwańska, Aleksandra; Kulbat, Aleksandra; Świercz, Kamila; Górska, Dominika; Majcher, Magdalena; Kulbat, Mateusz; Majcher, Monika; Brzychczy, Piotr; Pikulicka, Agata; Sierpień, Małgorzata (Journal of Education, Health and Sport, 2023)
Introduction Acne vulgaris is the most common skin disease that affects the majority of the population. Concepts on the pathogenesis of this disease have been changing over the years, as evidenced by the current indication of the precedence of inflammatory or immunological processes over disorders of keratinization of the outlets of hair and sebaceous units during the formation of acne lesions. Due to the complexity of the etiopathogenesis of acne vulgaris, the selection of appropriate therapeutic management is sometimes complicated. In addition, the process of treating the disease is multifaceted and time-consuming. Purpose The purpose of this review is to present the current state of knowledge on the effects of physical activity, diet and stress on acne vulgaris, as well as on the pathogenesis of acne vulgaris and the therapeutic management of patients suffering from this disease. Methods Literature was searched in PubMed and Google Scholarship databases. Publicly available books were searched. Results There is a proven precedence of inflammatory or immune processes over disorders of the keratinization of the estuaries of hair and sebaceous units during the formation of acne lesions. Conclusions Specialists should delve into the mechanism of the problem visible on the patient's skin to effectively and permanently cure the disease.